Public Service Management in North Buton District - Jopang Jopang; Zulfiah Larisu; Sumadi Dila (Jurnal Manajemen Pelayanan Publik, 2023)
The Regional Government Programme is accelerating bureaucratic reform for the development of electronic governance in information technology systems. It proves that the government is working to improve the quality of service to the public. Law No. 25 of 2009 on public services as the fulfilment of the demands of the public in quality services efficient and effective. This, as a breakthrough and innovation was realized by the Regulation of the Minister of State Apparatus Public Service No. 53 of 2017 on the maintenance of public service goods (MPP) in the implementation of services for the community in North Buton district with a total of 297 services in 53 instances and a total number of 97.690 visitors. The problems faced in the public service mall are related to the servers used and still minimality of the community in using the facility.